Distributed Autonomous Robotic Systems The 10th International Symposium - Martinoli, Alcherio.; Martinoli, Alcherio.; Mondada, Francesco.; Mondada, Francesco.; Correll, Nikolaus.; Correll, Nikolaus.; Mermoud, Grégory.; Mermoud, Grégory.; Egerstedt, Magnus.; Egerstedt, Magnus.; Hsieh, M. Ani.; Hsieh, M. Ani.; et al. (Springer Tracts in Advanced Robotics,, 2013)
Distributed robotics is a rapidly growing, interdisciplinary research area lying at the intersection of computer science, communication and control systems, and electrical and mechanical engineering. The goal of the Symposium on Distributed Autonomous Robotic Systems (DARS) is to exchange and stimulate research ideas to realize advanced distributed robotic systems. This volume of proceedings includes 43 original contributions presented at the Tenth International Symposium on Distributed Autonomous Robotic Systems (DARS 2010), which was held in November 2010 at the École Polytechnique Fédérale de Lausanne (EPFL), Switzerland. The selected papers in this volume are authored by leading researchers from Asia, Australia, Europa, and the Americas, thereby providing a broad coverage and perspective of the state-of-the-art technologies, algorithms, system architectures, and applications in distributed robotic systems. The book is organized into four parts, each representing one critical and long-term research thrust in the multi-robot community: distributed sensing (Part I); localization, navigation, and formations (Part II); coordination algorithms and formal methods (Part III); modularity, distributed manipulation, and platforms (Part IV).